Elite athletes with COVID-19 - Predictors of the course of disease - Krzywanski, J.; Mikulski, T.; Krysztofiak, H.; Pokrywka, A.; Mlynczak, M.; Malek, L. A.; Kwiatkowska, D.; Kuchar, E. (Journal of Science and Medicine in Sport, 2022)
Objectives: The aim of the study was to identify predictors determining the course of COVID-19 and antibody response in elite athletes. Design: Observational study. Methods: Routine medical screening with physical examination, resting ECG, and laboratory tests including antibody response was performed 12-68 days after the diagnosis of COVID-19 in 111 athletes of different sports. Results: Clinical symptoms were observed in 84% of subjects. The severity of COVID-19 was mild in 82% of athletes and moderate in 2% of cases. Athletes aged above 26 and male were more likely to develop symptomatic COVID-19. Asymptomatic subjects were younger and predominantly female. In 18% of subjects, symptoms were still present 20 (12-68) days (median and range) since positive diagnosis. Antibody response was observed in 88% of athletes, and its magnitude correlated with time since diagnosis of COVID-19 (RT-PCR), fatigue, fever, and conjunctivitis. There were no differences in antibody response between groups distinguished by sports discipline (p = 0.50), and sex (p = 0.59), and antibody response did not correlate with BMI (p = 0.12), age (p = 0.13), the number of symptoms (p = 0.43) or their duration (p = 0.19). Conclusions: The severity of COVID-19 in elite athletes is predominantly mild and without complications. Athletes can return to sport after two symptom-free weeks and additional heart screening is usually not required. Determination of antibodies has been shown to be a useful indicator of a previous COVID-19 disease, and some symptoms can be used as predictors of antibody response.